THE USE OF SIGIL SOFTWARE IN THE DEVELOPMENT OF GUIDED DISCOVERY LEARNING-BASED E-MODULES FOR TEACHERS OF CHEMICAL MGMP PADANG PANJANG - Budhi Oktavia; Ahmad Fauzi; Rahadian Zainul; Firmansyah Khairul Kamal (Fakultas MIPA Universitas Negeri Padang, 2022)
Sigil is an e-module creation software that can be used by high school teachers to help provide various teaching materials. However, the teacher's ability to use the Sigil software is still low where the teacher is still not able to apply the teaching materials in this e-module. E-modules can be used in online learning. One of the learning models that can be used is the Guided Discovery Learning (GDL) learning model. For this reason, society service for chemistry teachers who are members of the Padang Panjang Chemistry MGMP has been carried out in the form of a GDL-based e-module development workshop using the Sigil application. After the activity, it was found that the teacher understood and was able to create a GDL-based e-module using Sigil.